Causes,effects of and probable solutions to examination malpractices in Nigeria: a csae study of the west African examination council (2008)
The foci of this investigation were the causes, effect of and probable solutions to examination malpractices in Abeokuta metropolis in Nigeria using west African examination council as a case study. Stratefied sampling technique was employed to obtain the various classes of respondents. The total of 350 respondents was used in the study. A segmented single instrument was used for data collection. The data was analyzed using descriptive and non-parametric statistics. Based on the findings which include non-completion of the syllabi, over-crowdedness, poor teacher quality among others, the recommendations made include adequate covergae of syllabi, improved parental commitment towards wards' educational development, commitment to training and retraining of teachers to improve the quality f teaching and learning as well as undiluted application of Act 33 of 1999 on examination malpractices in Nigeria.